Effectiveness of Seismic Isolation for Long-Period Structures Subject to Far-Field and Near-Field Excitations - Anajafi, Hamidreza; Poursadr, Kiavash; Roohi, Milad; Santini-Bell, Erin (Frontiers in Built Environment, 2020)
This study evaluates primarily the effectiveness of seismic isolation for structures with intermediate and relatively long non-isolated periods (e.g., bridges with tall piers) subjected to near-field (NF) and far-field (FF) excitations. The inelastic response spectrum approach is used to systematically evaluate the effects of the two fundamental aspects of seismic isolation, i.e., period lengthening and lateral-strength reduction on the force and displacement demands on isolated structures. To validate the results, the real-world isolated Rudshur bridge with a relatively flexible (long-period) substructure is studied. Additional isolated and non-isolated variants of the Rudshur bridge with different initial periods are also developed. 20 FF (non-pulse) and 20 NF (pulse type) ground motions are used for nonlinear response history analyses. The results illustrate that when designed properly, seismic isolation can effectively reduce the mean base shear and acceleration responses of structures with relatively long non-isolated periods under FF excitations. For these structures, seismic isolation does not significantly increase the mean displacement responses under FF excitations, and even for particular cases, can reduce them. For the NF excitations, seismic isolation can significantly reduce the mean base shear responses of intermediate- to long-period structures. In some cases, this reduction is more significant than that for FF excitations. However, when the initial period of the isolated structure is relatively long (e.g., greater than 2.5 s), NF excitations can impose significantly large mean displacement demands on the superstructure (i.e., as great as 1.0 m for the studied cases). For NF excitations, a range of initial period (e.g., 1.5-2.5 s for the studied ground motions) and lateral yield-strength (e.g., 10-15% of the seismically effective weight) exists for the isolation system parameters that can noticeably reduce mean acceleration and base shear responses while mean displacement responses of the isolated superstructure remain within ranges used in practice. The inelastic-spectrum approach as used in this paper can reasonably predict these isolation system parameters.